How do young learners learn a new language? - Eva Faliyanti; Fenny Thresia; Fitri Palupi Kusumawati (SIGEH ELT : Journal of Literature and Linguistics, 2021)
Language can be defined as an organized system of arbitrary signals and rule-governed structures that are used as a means for communication. Language occurs both receptively and expressively through reading, listening, writing, and speaking. In order to become fully functioning members of school and society, children must learn the elements, the rules, the structure, and the conventions of this system. Children are often more enthusiastic and lively as learners but they also lose interest more quickly and are less able to keep themselves motivated on tasks they find difficult and often seem less embarrassed than adults at talking in a new language. Teaching English to young learners brings a number of challenges. Starting to learn English at an earlier age may not bring automatic improvements to proficiency levels, unless teacher education and secondary language teaching both adapt to meet the challenges of the new situation.